Condition monitoring of train wheel wear and track forces : a case study - Palo, Mikael; Arasteh Khouy, Iman; Schunnesson, Håkan; Larsson, Dan (Luleå tekniska universitet, Drift, underhåll och akustik, 2010)
One of the major failure modes in the railway industry is wheel wear. Wheel wear affects the dynamic characteristics of vehicles and the dynamic force impact on the rail, and can in worst cases scenario cause derailment. The wheel conditions also influences the wear and required maintenance on the rail. In this paper the correlation of wear rate and dynamic force between wheel and rail is studied to specify the most costeffective wheel maintenance interval. Two cars, total of sixteen wheels, were selected. In order to calculate the wear trend, measurements have been performed, by MiniProfTM, for a period of 12 months with the cars in traffic. During the same time period, the trend of track forces from the two cars has been obtained from the research station, outside Luleå, Sweden. Using the trends from wheel wear and track force in combination to form maintenance planning for wheels are discussed. Godkänd; 2010; 20100823 (ysko)